2015
DOI: 10.1103/physrevlett.114.233401
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Aluminum Atoms Floating on the Surface of Helium Nanodroplets

Abstract: Metal atoms have proved to be sensitive probes of the properties of superfluid helium nanodroplets. To date, all experiments on the doping of helium droplets have concentrated on the attachment of metal atoms in their ground electronic states. Here we report the first examples of metal atoms in excited states becoming attached to helium nanodroplets. The atoms in question are aluminum, and they have been generated by laser ablation in a metastable quartet state, which attaches to and remains on the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…This concept of multi-center growth is discussed in Section 3.3. Dopants can be introduced in the HND by pick-up, where the HND collects vaporized dopants on the fly-by, by electrospray ionization followed by trapping [80] or ion deceleration [81], by laser ablation techniques [82][83][84], or by merged beams [85]. While dopant efficiencies for neutrals are usually high, they can go down for the pickup of ions with high kinetic energies [86].…”
Section: Pickup Of Atoms and Molecules (Dopants)mentioning
confidence: 99%
“…This concept of multi-center growth is discussed in Section 3.3. Dopants can be introduced in the HND by pick-up, where the HND collects vaporized dopants on the fly-by, by electrospray ionization followed by trapping [80] or ion deceleration [81], by laser ablation techniques [82][83][84], or by merged beams [85]. While dopant efficiencies for neutrals are usually high, they can go down for the pickup of ions with high kinetic energies [86].…”
Section: Pickup Of Atoms and Molecules (Dopants)mentioning
confidence: 99%
“…We have shown that populations in the 2 P SO sub-levels of In atoms inside helium nanodroplets are frozen after pickup. Although absence of SO relaxation has been found before for metastable aluminum atoms on the weakly interacting droplet surface, 15 the lack of relaxation for species fully immersed in the droplet is rather surprising. In our case, the strong perturbation imposed on atoms in the droplet's interior is evidenced by blue shifts of several thousand wavenumbers, in striking contrast to only a few wavenumbers for atoms on the surface.…”
Section: ■ Conclusionmentioning
confidence: 85%
“…Photoexcitation of atoms in He N is often followed by population transfer to lower states, as was observed for surface-located alkali-metal atoms and for fully immersed metal atoms. , Electronic relaxation can be accompanied by reorientation of angular momenta, leading to spin relaxations within the SO manifold and transitions to different spin multiplicities. The large amount of excess energy introduced into the system at photoexcitation in combination with an increased density of states for higher electronic states presumably leads to couplings between dopant–He-atom potential energy surfaces at close distances, which might induce transitions to lower dopant states. , Without photoexcitation and on the weakly interacting droplet surface, spin reorientation seems to be low, resulting in long spin-lifetimes of alkali-metal atoms in the electronic ground state , and metastable quartet states of aluminum atoms that are picked up in excited states …”
Section: Introductionmentioning
confidence: 99%
“…Generally, the dopant material goes toward the center of the droplet where it condenses into a cluster. Several species have been identified that are most stable on the exterior of the helium droplet, including aluminum atoms in an excited state, but the ground-state aluminum atoms are expected to reside at the center of the droplet . The cluster size is a function of how many dopant atoms or molecules the droplet intercepts and therefore depends upon droplet size, velocity, and the vapor density of the dopant.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to various single-component particles, superfluid helium droplet assembly (SHeDA) has also been used to generate core–shell particles of various combinations including magnesium/copper, magnesium/perfluoropolyether, and silver/gold . Although the instrument is unique, other groups do similar work with organics, metals, and various other dopant materials. , By making aluminum particles with this method, we bridge the gap between aluminum clusters and conventional aluminum nanoparticles to understand how aluminum particles behave at their lower size limit.…”
Section: Introductionmentioning
confidence: 99%